Mediating Effect of Investments on Medical Sales Representatives between Personal Selling Tactics through Medical Doctors and Organizational Sales Performance - Sayandhan, T. (2023)
Globally and in Sri Lanka, pharmaceutical companies are not allowed to promote the product directly to the end user, the patients, due to the regulatory guidelines issued by the regulatory authority. Hence, the pharmaceutical industry uses medical sales representatives as a critical method to promote the products to doctors; in return, the doctors prescribe the product to patients with many investments spent on promotions. However, the return on the investment made on the medical sales representatives to induce them to promote company medical products to doctors with the expectation of prescribing organization products to end-user (patients) needs to be evaluated in measuring marketing effectiveness. Based on the above premise, this study proposal aims to investigate if the organizational investments in medical sales representatives’ personal selling through medical doctor promotions to promote corporate products (brands) to their end-users (patients) significantly help the organizational sales performance. This study uses a deductive research approach with a quantitative quasiexperimental design, this DBA study aims to administer a survey with a sample of 338 respondents selected based on the random sampling method. The population represents senior managers, middle managers, and medical sales representatives are randomly chosen from three hundred and sixty-eight registered pharmaceutical companies operating in Sri Lanka. Data was collected using a structured questionnaire with scales (1-5) to measure each item. Data were processed for analysis using Microsoft Excel 2019 and eventually uploaded to R-Studio (4.1.2 version) to analyze data to compute correlation, linear regression, and path analysis. Secondary data were collected from the industry depository about the organizational performance in annual sales turnover and market share for at least the last five years. The findings reveal that personal selling by medical sales representative positively influence by 68% and each 1 unit increase organizational sales by 1.43 units. Investment made on medical sales representatives positively influence by 57% of the organizational sales performance and each 1 unit of investment yield 2.8 times of organizational sales performance. There have been a few preidentified limitations associated with the study: the number of variables included for the investigation, sample size, and time availability are a few